Experimental Study on a Solar Energy–Multi-Energy Complementary Heating System for Independent Dwellings in Southern Xinjiang - Jie Li; Qian Yang; Hong Chen; Sihui Huang (Energies)
This study proposes a multi-energy complementary heating system that uses solar energy combined with biomass energy as the main heat source, with electricity as an auxiliary heat source. The system aims to tackle the low efficiency, high energy consumption, and pollution associated with traditional heating methods in rural southern Xinjiang, enhancing performance and productivity. It is designed to operate in five modes based on the region’s climate and building heat load requirements. An experimental platform was set up in eight rural households in Tumushuk City, Xinjiang, where winter heating tests were conducted. The goal of this study was to analyze the economic and environmental benefits of the system. The results showed that the energy utilization efficiencies of the five modes were 56.84%, 74.34%, 70.1%, 63.13%, and 59.68%. The corresponding CO2 emissions were 3.56 kg/d, 45.09 kg/d, 105.75 kg/d, 30.97 kg/d, and 76.79 kg/d. The environmental and economic costs for each mode were 0.0493 USD/d, 0.6398 USD/d, 1.5029 USD/d, 0.4384 USD/d, and 1.0905 USD/d. It is clear that as an auxiliary heat source, biomass energy is more beneficial than electricity. All five modes maintained indoor temperatures of 18 °C or higher, meeting winter heating needs in cold regions. The results of this study provide important data support for the promotion and application of solar and biomass heating systems in the rural areas of southern Xinjiang and also provide valuable references for solving the problem of decentralized heating in rural areas.